2017
DOI: 10.3168/jds.2017-12777
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from dairy lagoons in the western United States

Abstract: Methane generation from dairy liquid storage systems is a major source of agricultural greenhouse gas emissions. However, little on-farm research has been conducted to estimate and determine the factors that may affect these emissions. Six lagoons in south-central Idaho were monitored for 1 yr, with CH emissions estimated by inverse dispersion modeling. Lagoon characteristics thought to contribute to CH emissions were also monitored over this time period. Average emissions from the lagoons ranged from 30 to 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 48 publications
4
25
3
Order By: Relevance
“…In contrast to the present study, other measurements of liquid manure storage (settling basin and anaerobic lagoon or manure tanks) in the western United States and Canada have indicated that US EPA predictions of annual manure CH 4 emissions may be underestimating on-farm emissions by up to 60% (Baldé et al, 2016;Leytem et al, 2017). A review of field-based studies on greenhouse gas emissions from dairy manure management also suggested that current CH 4 emission factors generally underestimate emissions from liquid manuremanagement systems (Owen and Silver, 2015).…”
Section: Open-path Ch 4 Estimates Broadly Tracked Monthly Us Epa Esticontrasting
confidence: 95%
See 1 more Smart Citation
“…In contrast to the present study, other measurements of liquid manure storage (settling basin and anaerobic lagoon or manure tanks) in the western United States and Canada have indicated that US EPA predictions of annual manure CH 4 emissions may be underestimating on-farm emissions by up to 60% (Baldé et al, 2016;Leytem et al, 2017). A review of field-based studies on greenhouse gas emissions from dairy manure management also suggested that current CH 4 emission factors generally underestimate emissions from liquid manuremanagement systems (Owen and Silver, 2015).…”
Section: Open-path Ch 4 Estimates Broadly Tracked Monthly Us Epa Esticontrasting
confidence: 95%
“…On dairy 2, the settling basin was the largest source of CH 4 emis- sions from liquid manure storage during the summer measurement period, whereas the anaerobic lagoon was the largest source of CH 4 emissions during the winter measurement period. Leytem et al (2017) and Borhan et al (2011) observed that settling basins generated more CH 4 than anaerobic lagoons during the summer but not the winter measurement period on 2 different dairies. Leytem et al (2017) suggested that CH 4 emissions from settling basins may be more affected by ambient temperature than CH 4 emissions from anaerobic lagoons because of their relatively smaller storage volume.…”
Section: Methane Emissions Varied Between and Within Source Areamentioning
confidence: 99%
“…For example, path lengths in the 10 to 100 m range are often reported in agricultural emissions research, particularly for targeted measurements of biogas systems [1], manure management systems [11][12][13], or grazing cattle [14]. Where the research site permits, longer path lengths are used [2,15], which our data suggest would have lower bias. Another study used a higher range of path-integrated CH 4 , from 529 to 2500 ppm·m, to calibrate an OP-TDL and it was found to be accurate and in good agreement with another open-path spectrometer, but that study did not focus on measurements below the calibrated range [16].…”
Section: Discussionmentioning
confidence: 73%
“…Rather than relying on only a couple point source releases, tracer gas could be released as a line or grid source along the border of liquid manure management areas or animal housing fence lines (Lamb et al, 1995;McGinn et al, 2006). Increasing the flow rate of tracer gas from 15 slpm by several factors would improve signal-to-noise ratios of tracer enhancements.…”
Section: Future Workmentioning
confidence: 99%
“…Application of tracer gases in agricultural studies have involved insertion of a sulfur hexafluoride (SF 6 ) permeation tube into the rumen of a cow with subsequent collection of time-integrated breath samples (Grainger et al, 2007). Inverse-dispersion techniques have employed line-source releases of SF 6 within a dairy farm combined with open-path measurements to understand whole-site emissions (McGinn et al, 2006). Release of a tracer gas directly into the atmosphere, 2-3 m above ground level, can be used to determine and distinguish CH 4 emissions from various sources within a site .…”
Section: Introductionmentioning
confidence: 99%